2013
DOI: 10.13168/agg.2013.0009
|View full text |Cite
|
Sign up to set email alerts
|

Silver and-or copper vermiculites and their antibacterial effect

Abstract: Vermiculite (V) from Brazil with aqueous solutions AgNO 3 and/or Cu(NO 3 ) 2 was used for preparation of nanocomposites V/Ag, V/Cu, V/AgCu and V/CuAg using two procedures and their effect on bacteria was compared. Structural changes were evaluated using X-ray diffraction (XRD) analysis, Infrared spectroscopy (IRS) and Scanning electron microscopy (SEM). Elemental chemical composition was determined using X-ray fluorescence (XRF) analysis and the solutions were analyzed by Atomic emission spectroscopy with indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Their porous structures comprise silicate layers organized in a 1 to 2 conformation (one aluminum octahedral sheet is sandwiched between two silicate tetrahedral ones). Such conformation leads to the formation of interlayer gaps, which mainly include cations to counterbalance the negative charge of the siloxamic cavities of vermiculite surfaces [16,17]. Electrostatically interacting metal ions at planar sites (outer-sphere complexes) can be efficiently exchanged.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their porous structures comprise silicate layers organized in a 1 to 2 conformation (one aluminum octahedral sheet is sandwiched between two silicate tetrahedral ones). Such conformation leads to the formation of interlayer gaps, which mainly include cations to counterbalance the negative charge of the siloxamic cavities of vermiculite surfaces [16,17]. Electrostatically interacting metal ions at planar sites (outer-sphere complexes) can be efficiently exchanged.…”
Section: Introductionmentioning
confidence: 99%
“…Electrostatically interacting metal ions at planar sites (outer-sphere complexes) can be efficiently exchanged. For instance, it was reported that silver ions exchange with Na + ions [17] and, remarkably, can exist on the vermiculite surfaces both in the Ag + and Ag 0 forms [4,5]. Thus, vermiculite has the potential to be used as a low-cost template for the fabrication of complex silver substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Fusion of metallic nanoparticles in the structure of aluminosilicates is a relatively new approach in the synthesis of nanoparticles, few reports have been presented thus far on this topic. Hundakova presented the synthesis of silver and copper vermiculites and tested their antibacterial effects against the two bacterial groups [31]. The method still follows the wet chemical process but vermiculite is used to stabilize the nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Due to structural properties the clay minerals are suitable substrates for various inorganic and/or organic constituents. Vermiculite is occasionally used as silver or copper particles support [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%